Case report: Infant with a Fast-growing Soft Tissue Tumor on the Thumb, Revealing a PLAG1-positive Connatal Lipoblastoma - Deeg, Susanne; Wessel, Lucas; Martel, Richard; Porubsky, Stefan; Svoboda, Daniel (Klinische Pädiatrie, 2020)
At the age of 4 months, an infant was presented to us with a nodular subcutaneous tumor on the right thumb measuring 2cm, already seen prenatally via ultrasound. An MRI in sedation performed at the age of 4.5 months had no diagnostic specificity. By a biopsy at the age of 5 months malignancy could be excluded. Finally at the age of 16 months the tumor which had meanwhile grown to a monstrous size (5 cm of diameter) could be entirely removed by microsurgical technique maintaining the integrity of all intrinsic structures. The diagnosis of myxoid lipoblastoma was confirmed. According to literature, Lipoblastomas often present as connatal rapid growing soft tissue tumors and are benign. Total removal is essential for avoiding a local recurrence.
Keywords: tumor; hand; lipoblastoma; myxoid; connatal